Sequence variation among populations of sawfishes (Pristiformes: Pristidae) from Indonesia and Australia - SUTARNO SUTARNO; A. BUDIHARJO; A.D. SETYAWAN; A.J. LYMBERY (Society for Indonesian Biodiversity, 2017)
Sutarno, Budiharjo A, Setyawan AD, Lymbery AJ. 2017. Sequence variation among populations of sawfishes (Pristiformes: Pristidae) from Indonesia and Australia. Biodiversitas 18: 850-856. The sawfishes (Pristiformes: Pristidae) are very rare and critically endangered species globally, calling for conservation efforts around the world. This species is taxonomically interesting because molecular research in recent years has led to re-groupings in some species. The aim of this research was to sequence the control region (CR) of mitochondrial DNA of sawfishes from Indonesia and Australia, compare the sequences between samples, and construct phylogenetic trees to know the relationship of those samples. To achieve these aims, dried rostra of samples from both countries are collected, total DNA were purified and amplified using PCR, followed by sequencing reaction. The sequence data were then lined followed by constructing phylogenetic trees. The results of the BLASTN and phylogenetic tree analysis found two species, the all Australian samples belong to Pristis pristis (formerly P. microdon), one Indonesian sample also belongs to P. pristis, while the other Indonesian samples belong to Anoxypristis cuspidata.